Application Analysis of Space-Based Relay in Land Resources Satellite Image Acquisition - Huibing WANG; Zuoya ZHENG; Sida OUYANG; Yue ZHANG; Chao YANG; Yu HUANG (天地一体化信息网络)
With the analysis of the main factors aff ecting the image acquisition of land remote sensing satellite, the satellite image data transmission application mode based on space-based relay was proposed to solve the bottleneck problem of satellite-ground receiving.Through simulation analysis and quantitative calculation, the application eff ect of relay transmission was calculated.The results showed that relay transmission could improved the visible time of satellite data receiving, thus greatly improved the total amount of image acquisition, and eff ectived perform the satellite operation effi ciency.